Load bearing capacity of prefinished prefabricated volumetric construction (PPVC) shear key connections - Ong, Kai Hong (Nanyang Technological University, 2021)
Prefabricated Prefinished Volumetric Construction (PPVC) is widely known to be the modern and futuristic form of construction that has been seeing a rapid growth in popularity as the go to method for construction. It brings to the table quick, efficient, and environmentally friendly site advantages over other forms of construction that is becoming the hot trend for many projects all over Singapore. As with every construction method, frameworks must be set in place by the appropriate authorities like the Building and Construction Authority (BCA) to ensure that all contractors embarking on such projects have a reliable set of design criteria to follow and adhere to. This is to ensure that the buildings constructed using PPVC are safe and meet the required performance standards for its residents and tenants. However, there is a lack of specifications and guidelines for specific components of the PPVC system. More specifically, the design criteria and calculations for shear keys required in the PPVC building connection system have not been fully elaborated by BCA. Furthermore, limited studies have been done on the load-bearing capacity of current PPVC connections and how its performance will affect the building’s overall structural integrity. This project will research on the current model of shear keys being utilised in PPVC structures and determine its effectiveness in withstanding shear stress. To further complement the tests’ accuracy, ANSYS finite element analysis simulations will also be conducted concurrently to predict the projected shear stresses as well as any future possible improvements to the current shear key design. This paper will provide insight on the shear strength capacity of the current shear key model used by TeamBuild Construction, as well as providing an improvement to the current shear key design. The project report consists of two reports, ST-38AB-1 and ST-38AB-2 with this paper being ST-38AB-2.